Brain structures and networks responsible for stimulation‐induced memory flashbacks during forniceal deep brain stimulation for Alzheimer's disease. Issue 5 (21st January 2021) - Germann, Jürgen; Elias, Gavin J.B.; Boutet, Alexandre; Narang, Keshav; Neudorfer, Clemens; Horn, Andreas; Loh, Aaron; Deeb, Wissam; Salvato, Bryan; Almeida, Leonardo; Foote, Kelly D.; Rosenberg, Paul B.; et al.
Abstract: Introduction: Fornix deep brain stimulation (fx‐DBS) is under investigation for treatment of Alzheimer's disease (AD). We investigated the anatomic correlates of flashback phenomena that were reported previously during acute diencephalic stimulation. Methods: Thirty‐nine patients with mild AD who took part in a prior fx‐DBS trial (NCT01608061) were studied. After localizing patients' implanted electrodes and modeling the volume of tissue activated (VTA) by DBS during systematic stimulation testing, we performed (1) voxel‐wise VTA mapping to identify flashback‐associated zones; (2) machine learning–based prediction of flashback occurrence given VTA overlap with specific structures; (3) normative functional connectomics to define flashback‐associated brain‐wide networks. Results: A distinct diencephalic region was associated with greater flashback likelihood. Fornix, bed nucleus of stria terminalis, and anterior commissure involvement predicted memory events with 72% accuracy. Flashback‐inducing stimulation exhibited greater functional connectivity to a network of memory‐evoking and autobiographical memory‐related sites. Discussion: These results clarify the neuroanatomical substrates of stimulation‐evoked flashbacks.